Emigration of Nepalese People and Its Impact - Kunwar, Laxman Singh (Economic Journal of Development Issues, 2017)
This paper reflects the emigration history of Nepalese people and their destinations with role of remittances in country of origin (Nepal). The number of emigrants and share of remittances in terms of GDP has been increased but at the same time various negative impacts have been emerged in Nepalese society. In addition trade deficit has been increased and Nepalese emigrants who are working abroad are not being able to receive their rights at their working place. Discriminations in terms of earning and other privileges are common for Nepalese emigrants and due lack of skills, trainings and low level of education mainly 3D (Difficult, Dirty, Dangerous) jobs secured at their working places, as a result the earning/remittances are also low. This paper is based on secondary sources of information and briefly explains the history of emigration and its impacts in socio-economic sectors of Nepal. Economic Journal of Development Issues Vol. 19 & 20 No. 1-2 (2015) Combined Issue, Page: 77-82